2010
DOI: 10.2147/ijwh.s12857
|View full text |Cite
|
Sign up to set email alerts
|

Trinidadian women’s knowledge, perceptions, and preferences regarding cesarean section: How do they make choices?

Abstract: ObjectivesThe objective of this study is to determine the awareness of perception and attitude toward cesarean section (CS) in a high-user setting.Design and methodsA cross-sectional design using multistage sampling methods was used to select participants from antenatal and postnatal clinics in a primary health care setting in north Trinidad. A multi-item structured questionnaire was designed and administered by in-depth interviews. Sociodemographic data and data about history of previous pregnancies and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Information given to women was most commonly provided by doctors and related mostly to procedural matters rather than focusing on the risks and benefits linked with VBAC. Women described that information was not provided routinely and they had to seek it actively, which is disappointing given the number of studies showing that education of all women in the antenatal period (including those with a previous CS) improves birth outcome (Maimburg et al, 2010) and is appreciated and requested by nulliparous and multiparous women alike (Mungrue et al, 2010). For example, relaxation and birth preparation classes, which have led to a reduction in CS rates in nulliparous women (Khunpradit el al., 2011), and psycho-educational group sessions for women experiencing an intense fear of childbirth (Salmela-Aro et al, 2012) could also be tried with women following previous CS.…”
Section: Introductionmentioning
confidence: 99%
“…Information given to women was most commonly provided by doctors and related mostly to procedural matters rather than focusing on the risks and benefits linked with VBAC. Women described that information was not provided routinely and they had to seek it actively, which is disappointing given the number of studies showing that education of all women in the antenatal period (including those with a previous CS) improves birth outcome (Maimburg et al, 2010) and is appreciated and requested by nulliparous and multiparous women alike (Mungrue et al, 2010). For example, relaxation and birth preparation classes, which have led to a reduction in CS rates in nulliparous women (Khunpradit el al., 2011), and psycho-educational group sessions for women experiencing an intense fear of childbirth (Salmela-Aro et al, 2012) could also be tried with women following previous CS.…”
Section: Introductionmentioning
confidence: 99%
“…Prathima (2014) found that the person who has been giving birth more than once has more knowledge and better understanding. Mungrue et al (2010) show that patient who has had caesarean section has a better understanding than a patient who has not had a caesarean section. A patient who gets information directly from doctor also has a better understanding and more knowledge related to caesarean section.…”
Section: Patient's Experienceaffects Patient Comprehension Ofcaesareamentioning
confidence: 95%
“…It appears that the high rate of cesarean delivery in Iran is a complex phenomenon. Thus, educational interventions to reduce the rate of cesarean delivery, improve the quality of routine vaginal delivery services, and change mothers' outlooks regarding the mode of delivery are essential [22]. Consequently, an instrument carefully assessing factors that affect the choice of delivery methods by mothers is required.…”
Section: Introductionmentioning
confidence: 99%